Efficacy and Safety of the Low-molecular Heparin in Treatment and Prevention of the Acute Coronary Syndrome - Katerenchuk I.; Tsyhanenko I.; Katerenchuk O. (Львівський клінічний вісник)
Introduction. For a long time, the main medication for treating and preventing of thrombotic complications was unfractionated heparin (UFH). However, despite its high efficiency, UFH has a number of disadvantages and side effects. Significant advantages over UFH are low molecular weight heparins or low molecular weight heparins (LMWH). LMWH is a product of enzymatic or chemical depolymerization of conventional heparin. The low molecular weight fractions of heparin obtained during the polymerization process have new pharmacodynamic properties. Today about 10 drugs of LMWH are used. They are obtained by various methods of depolymerization of UFH, resulting in fractions with a lower molecular weight (from 4000 to 6500 daltons). Aim. To review and analyze the current knowledge about the effectiveness and safety of use of LMWH for the treatment and prevention of acute coronary syndrome. Materials and methods. The content analysis, method of system and comparative analysis, the bibliosemantic method of study of actual scientific researches concerning the efficiency and safety of the use of LMWH for the treatment and prevention of acute coronary syndrome has been used. Comparison of the effectiveness of various preparations of low molecular weight heparins is carried out taking into account the results of multicenter studies. The results indicate that LMWH is an effective and safe remedy for the treatment of acute coronary syndrome and preventing coronary events in patients at different risk levels. LMWH are much less than UFH binding to plasma proteins that can neutralize their antithrombotic activity. The low affinity of LMWH to plasma proteins that neutralize heparin is due to their high bioavailability of low doses and greater predictability of anticoagulant response at high doses. LMWH have longer antithrombotic activity than UFH. While the half-life in blood plasma (T1 / 2) of UFH is, if judged by its activity against factor Xa, 50-60 minutes, T1 / 2 of LMWH after intravenous administration is within 1.5-4.5 hours. Significant duration of antithrombotic effect of LMWH allows them to be assigned once or twice a day. The bioavailability of most of the LMWH after deep subcutaneous injection is about 90.0%, whereas in case of UFH it is 15.0 – 20.0%. All of the considered features of pharmacokinetics and pharmacodynamics of LMFH suggest their undoubted advantage over UFH, which consists in the fact that with both – preventive and therapeutic purpose – subcutaneously constant dose can be administered. In addition, LMWH are resistant to inactivating of factor 4 of thrombocytes and do not increase their arrreation under the influence of various inductors. In the case of LMWH, the frequency of thrombocytopenia is much lower. Conclusions. LMWH is an effective and safe medication of the treatment of acute coronary syndrome and for the preventing of coronary events in patients at different risk levels.